TYPES OF SIMILES ACCORDING TO THE CONTENT IN ALISHER NAVOY’S EPIC “FARHAD AND SHIRIN (Scientific journal of the Fergana State University, 2024)
This article covers issues such as the study of simile constructions used in Navoi's works and their place in language development. The main goal of the research is to analyze the specific features of simile constructions and to reveal the linguistic and cultural aspects of simile devices used in Navoi’s epic “Farhod and Shirin”, in addition, to study the research conducted in world linguistics on simile devices. learning consists in reacting to analogical constructions by summarizing the ideas expressed. The similes used in Alisher Navoi’s epic “Farhad and Shirin” and the lexemes described in Manzar Abdulkhair’s “Annotated Dictionary of Navoi’s Works” (Tashkent 2018) were taken as the object of research. Linguistic analysis, descriptive, descriptive, comparative, lexicographic, semantic-stylistic and linguostatistical analysis methods were used in the research process.